High-rate silicon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611331830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]但是,现有硅基负极材料仍存在进一步改进的空间
[0017]本发明实施例提供的高倍率硅负极材料,通过在团聚形成的二次颗粒的多孔硅一次颗粒之间引入柔性纳米石墨微晶,通过柔性纳米石墨微晶之间相互搭接、交叠和/或桥连,在二次颗粒内部形成三维导电结构,有利于增加颗粒间有效导电接触、缩短电子传输路径并降低接触电阻,从而提高材料的导电性能和倍率性能;多孔硅一次颗粒内部的纳米孔隙与多孔硅一次颗粒间的残余空隙可共同为硅在嵌脱锂过程中的体积变化提供缓冲空间,降低颗粒开裂、粉化及导电接触失效的风险,从而改善循环稳定性;多孔硅一次颗粒表面还设置预碳包覆层,可减少相邻多孔硅一次颗粒之间的直接硅-硅接触以及多孔硅与电解液的直接接触,提高单颗粒界面稳定性和自身导电性。二次颗粒外表面的外层碳包覆层可减少电解液与硅材料的直接接触和界面副反应,同时与内部柔性纳米石墨微晶及预碳包覆层相互导电连通,有利于维持二次颗粒整体导电连续性。由此改善负极材料的首次库仑效率、循环稳定性及结构稳定性。本发明提出的高倍率硅负极材料,可用于锂离子电池负极,应用在新能源汽车动力电池、储能锂电池、消费电子锂电池等领域。
Smart Images

Figure CN122889732A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery anode technology, and in particular to a high-rate silicon anode material, its preparation method, and its application. Background Technology
[0002] With the increasing demands for energy density and fast charge / discharge performance of lithium-ion batteries from new energy vehicles, energy storage devices, and consumer electronics, silicon-based anode materials with high theoretical specific capacity have attracted widespread attention. Compared to traditional graphite anode materials, silicon has a higher theoretical specific capacity and is therefore considered one of the important anode materials for improving the energy density of lithium-ion batteries. However, silicon undergoes significant volume changes during charge and discharge, which can easily lead to cracking, pulverization, and failure of conductive contacts between silicon particles. Simultaneously, silicon itself has poor electronic conductivity, making it prone to significant polarization under high-rate charge / discharge conditions, thus affecting the material's rate performance and cycle stability.
[0003] To mitigate the volume change of silicon materials during cycling and improve their conductivity, existing technologies have proposed various improvement methods, such as porosification, carbon coating, and compositing with other conductive materials. For example, CN117650235A discloses a non-filled carbon-coated porous micron-based silicon anode material and its preparation method. This anode material includes a porous micron-based silicon core, a layer of metal nanoparticles disposed on the surface of the porous silicon core, and an outermost non-filled carbon coating layer. The porous silicon core can be polycrystalline silicon or silicon suboxide, and the external carbon coating layer improves the interfacial stability of the material. As another example, CN120308967A discloses a porous silicon-carbon composite anode material and its preparation method. Nano-silicon is deposited on the surface of carbon nanotubes (CNTs) via chemical vapor deposition to form a Si / CNTs composite. Subsequently, the Si / CNTs composite is mixed with resin materials and subjected to heat treatment to obtain a porous silicon-carbon anode material composed of silicon, carbon nanotubes, and carbon materials. This type of technology, by introducing carbon materials or carbon nanomaterials, can improve the conductivity and structural stability of silicon-based materials to a certain extent.
[0004] However, there is still room for improvement in existing silicon-based anode materials. On the one hand, when multiple porous silicon particles form an agglomeration structure, there are usually interparticle gaps between adjacent silicon particles. The existing outer carbon coating structure is mainly formed on the outside of the agglomerated particles, making it difficult to establish a continuous and stable interparticle electron transport pathway for the interparticle gaps inside the secondary particles. This results in relatively high electron transport resistance inside the secondary particles, which easily leads to increased polarization and local conductive contact failure under high-rate charge-discharge conditions. On the other hand, when the carbon coating layer is only placed on the outside of the secondary particles, the surface of the individual silicon particles inside the secondary particles may still be in direct contact with the electrolyte. During cycling, the solid electrolyte interface film is easily formed or repeatedly damaged, thereby increasing irreversible capacity loss. In addition, although the interparticle gaps can provide space for the volume expansion of silicon to a certain extent, if there is a lack of effective flexible conductive connection structure between the particles, the conductive contact of the silicon particles is still prone to loosening or even failure during repeated expansion and contraction, thus affecting the cycling performance and rate performance of the material.
[0005] Therefore, how to further improve the continuity of electron transport between primary and secondary particles of porous silicon, and reduce the direct contact between silicon and electrolyte, while taking into account the expansion buffer space of silicon materials, is a technical problem that still needs to be solved for existing silicon-based anode materials. Summary of the Invention
[0006] The purpose of this invention is to address the deficiencies of existing technologies by providing a high-rate silicon anode material, its preparation method, and its applications. This invention involves forming a pre-carbon coating layer on the surface of porous primary silicon particles and introducing flexible nano-graphite crystals between adjacent primary particles. This allows the flexible nano-graphite crystals to form conductive connections with the pre-carbon coating layer on the surfaces of multiple primary particles. Simultaneously, the flexible nano-graphite crystals overlap to form a three-dimensional conductive structure within the secondary particles. Furthermore, an outer carbon coating layer connects the internal conductive structure of the secondary particles with the outer carbon coating layer, thereby improving the overall electron transport continuity and rate performance of the material, and enhancing the interfacial and structural stability of the silicon particles during cycling.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a high-rate silicon anode material, the anode material comprising composite secondary particles, the composite secondary particles comprising: The structure consists of a secondary particle matrix formed by the aggregation of multiple porous primary silicon particles, flexible nano-graphite microcrystals, and an outer carbon coating layer. The surface of the porous silicon primary particles has a pre-carbon coating layer; There are interparticle gaps between adjacent porous silicon primary particles, and the flexible nano-graphite crystals are distributed in the interparticle gaps; wherein, at least some of the flexible nano-graphite crystals are in contact with the pre-carbon coating layer on the surface of two or more adjacent porous silicon primary particles at the same time, forming a conductive bridge between adjacent porous silicon primary particles; and the flexible nano-graphite crystals form a three-dimensional conductive structure inside the secondary particles through overlapping, interlocking and / or bridging. The outer carbon coating layer covers the outer surface of the secondary particle body; the outer carbon coating layer, the flexible nano-graphite microcrystals inside the secondary particle, and the pre-carbon coating layer on the surface of the porous silicon primary particle are electrically connected to each other, forming a conductive network that extends from the inside to the outside of the secondary particle.
[0008] Preferably, the porous silicon primary particles account for 50%-80% of the mass percentage of the high-rate silicon anode material, the flexible nano-graphite microcrystals account for 15%-40% of the mass percentage of the high-rate silicon anode material, and the outer carbon coating layer accounts for 2%-15% of the mass percentage of the high-rate silicon anode material.
[0009] Preferably, the particle size D50 of the porous silicon primary particles is 0.2-2.0 μm; the porous silicon primary particles have multiple nanopores inside, at least some of which are interconnected, the average pore size of the nanopores is 5-100 nm, and the porosity of the porous silicon primary particles is 20%-30%. The pre-carbon coating layer covers the surface of the porous silicon primary particles, and the thickness of the pre-carbon coating layer is 2-15 nm.
[0010] Preferably, the flexible nano-graphite crystallite comprises sheet-like stacked crystals, wherein the sheet diameter of the flexible nano-graphite crystallite is 20-200 nm and the thickness is 2-20 nm; The flexible nano-graphite microcrystals fill 30%-60% of the gaps between the particles; The secondary particles retain residual interparticle voids that were not filled by the flexible nano-graphite microcrystals.
[0011] Preferably, the particle size D50 of the secondary particle body is 5-15 μm; The outer carbon coating layer has a thickness of 2-15 nm, and the outer carbon coating layer covers at least 90% of the outer surface of the secondary particle body. The outer carbon coating layer includes at least one of the following: a graphite carbon layer, an amorphous carbon layer, or a carbon nanotube network layer.
[0012] In a second aspect, embodiments of the present invention provide a method for preparing the high-rate silicon anode material described in the first aspect above, the method comprising: S1, pre-treat the porous silicon primary particles and form a pre-carbon coating layer on the surface of the porous silicon primary particles by chemical vapor deposition to obtain pre-carbon coated porous silicon primary particles. S2, the flexible nano-graphite microcrystals and binder are dispersed in a solvent to obtain a filling slurry containing the flexible nano-graphite microcrystals, and the pre-carbon-coated porous silicon primary particles are mixed with the filling slurry to obtain a silicon-graphite mixed suspension. S3, the silicon-graphite mixed suspension is desolvated and agglomerated to form a secondary particle body by agglomerating multiple porous silicon primary particles, thereby obtaining a composite secondary particle body filled with flexible nano-graphite microcrystals; wherein, the flexible nano-graphite microcrystals are filled in the interparticle gaps between adjacent porous silicon primary particles. S4, the composite secondary particle body is mixed with the outer carbon-coated carbon source and heat-treated to form an outer carbon coating layer on the outer surface of the composite secondary particle body, thereby obtaining the high-rate silicon anode material.
[0013] Preferably, in step S1, the pretreatment includes: purifying and cleaning the porous silicon primary particles; placing the pretreated porous silicon primary particles in a chemical vapor deposition (CVD) apparatus, introducing a gaseous carbon source under inert gas protection, and performing CVD at 600-800 °C for 15-180 min to form a pre-carbon coating layer with a thickness of 2-15 nm on the surface of the porous silicon primary particles; wherein the gaseous carbon source includes at least one of methane, acetylene, or propylene. In step S2, the binder includes at least one of polyvinyl alcohol (PVA) or carboxymethyl cellulose (CMC), and the solvent includes deionized water or anhydrous ethanol; the dispersion time is 30-120 min; the mixing is performed by high-speed shear stirring at a speed of 1000-5000 r / min for 1-4 h. In step S3, the method for desolventizing and agglomerating includes spray drying; the inlet air temperature of the spray drying is 160-220 ℃, the outlet air temperature is 70-110 ℃, and the atomization pressure is 0.2-0.6 MPa; In step S4, the mixing is a dry mixing process, and the carbon source for the outer carbon coating includes at least one of coal tar pitch or petroleum pitch; the heat treatment is carried out under an inert atmosphere, with a heating rate of 2-8 ℃ / min, a heat treatment temperature of 850-1100 ℃, and a holding time of 1-5 h.
[0014] Preferably, in step S2, the apparent viscosity of the filler slurry at 25 °C is 500-5000 mPa·s; and the solid content of the filler slurry is 5%-30%.
[0015] Thirdly, embodiments of the present invention provide a negative electrode sheet comprising the high-rate silicon negative electrode material described in any of the first aspects above.
[0016] Fourthly, embodiments of the present invention provide a lithium-ion battery, including the negative electrode sheet described in the third aspect above.
[0017] The high-rate silicon anode material provided in this invention introduces flexible nano-graphite crystals between porous primary silicon particles that are agglomerated into secondary particles. These flexible nano-graphite crystals overlap, interlock, and / or bridge each other, forming a three-dimensional conductive structure within the secondary particles. This increases effective conductive contact between particles, shortens electron transport paths, and reduces contact resistance, thereby improving the material's conductivity and rate performance. The nanopores within the porous primary silicon particles and the residual voids between them provide a buffer space for volume changes during lithium insertion / extraction, reducing the risk of particle cracking, pulverization, and conductive contact failure, thus improving cycle stability. A pre-carbon coating layer is also provided on the surface of the porous primary silicon particles, reducing direct silicon-silicon contact between adjacent particles and direct contact between the porous silicon and the electrolyte, improving the interfacial stability and conductivity of individual particles. The outer carbon coating layer on the surface of the secondary particles reduces direct contact between the electrolyte and silicon material and interfacial side reactions, while simultaneously maintaining conductive connectivity with the internal flexible nano-graphite crystals and the pre-carbon coating layer, thus helping to maintain the overall conductive continuity of the secondary particles. This improves the initial coulombic efficiency, cycle stability, and structural stability of the anode material. The high-rate silicon anode material proposed in this invention can be used as a lithium-ion battery anode, with applications in new energy vehicle power batteries, energy storage lithium batteries, and consumer electronics lithium batteries. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the structure of the high-rate silicon anode material provided in an embodiment of the present invention; Figure 2 This is a graph comparing the cycle performance of Embodiment 1 and Comparative Example 1 of the present invention. Figure 3 This is a rate performance curve of Embodiment 1 of the present invention. Detailed Implementation
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0020] This invention provides a high-rate silicon anode material, its preparation method, and its application.
[0021] Figure 1 This is a schematic diagram of the structure of the high-rate silicon anode material provided in an embodiment of the present invention. The high-rate silicon anode material of the present invention includes composite secondary particles, specifically including: a secondary particle body formed by the agglomeration of multiple porous primary silicon particles, flexible nano-graphite microcrystals, and an outer carbon coating layer.
[0022] The porous silicon primary particles account for 50%-80% of the mass percentage of the high-rate silicon anode material, the flexible nano-graphite microcrystals account for 15%-40% of the mass percentage of the high-rate silicon anode material, and the outer carbon coating layer accounts for 2%-15% of the mass percentage of the high-rate silicon anode material.
[0023] The particle size D50 of the porous silicon primary particles is 0.2-2.0 μm; the particle size D50 of the secondary particle body formed by agglomeration is 5-15 μm, preferably 8-15 μm. The particle size of the secondary particle body refers to the particle size of the agglomerated particles after multiple porous silicon primary particles agglomerate and flexible nano-graphite microcrystals are distributed between the particles, before the formation of the outer carbon coating layer.
[0024] The porous silicon primary particles contain multiple nanopores, at least some of which are interconnected. The average pore size of the nanopores is 5-100 nm, preferably 10-50 nm. These nanopores provide an internal buffer space for the volume changes that occur during lithium insertion and extraction, thereby reducing the risk of cracking or pulverization of the primary particles caused by these volume changes. The porosity of the porous silicon primary particles is 20%-30%.
[0025] Preferably, the surface of the porous silicon primary particles has a pre-carbon coating layer; the pre-carbon coating layer covers the surface of the porous silicon primary particles, and the thickness of the pre-carbon coating layer is 2-15 nm. The pre-carbon coating layer can continuously or substantially continuously (e.g., coverage of over 80%) cover the surface of the porous silicon primary particles, and can partially extend to the pore wall surface communicating with the outer surface of the particles. The pre-carbon coating layer can reduce direct silicon-silicon contact between adjacent porous silicon primary particles and reduce direct contact between porous silicon and the electrolyte, thereby helping to reduce interfacial side reactions; simultaneously, the pre-carbon coating layer can also improve the electron transport capacity of the surface of a single porous silicon primary particle and provide a conductive interface for establishing a conductive connection between the flexible nano-graphite microcrystals and the porous silicon primary particles.
[0026] Interstices exist between adjacent porous silicon primary particles, and flexible nano-graphite crystallites are distributed within these interstices. At least some of these flexible nano-graphite crystallites simultaneously contact the pre-carbon coating layer on the surface of two or more adjacent porous silicon primary particles, forming conductive bridges between them. Furthermore, the flexible nano-graphite crystallites overlap, interlock, and / or bridge to form a three-dimensional conductive structure within the secondary particles. Through this structure, the flexible nano-graphite crystallites transform the original point or indirect contact between adjacent porous silicon primary particles into multi-point contact and conductive bridges involving multiple nano-graphite sheets, thereby increasing the effective electron transport interface between primary particles, shortening the electron transport path between particles, and reducing the contact resistance between particles. The flexible nano-graphite crystallites further interconnect multiple local conductive bridges through overlapping, interlocking, and / or bridging, which helps maintain the continuity of the electron transport pathway within the secondary particle body.
[0027] In one specific example, the flexible nanographite crystallizer comprises stacked sheet-like crystals with a sheet diameter of 20-200 nm and a thickness of 2-20 nm. Preferably, the sheet diameter is 50-120 nm and the thickness is 3-10 nm. The sheet diameter of the flexible nanographite crystallizer is smaller than the particle size of the secondary particle bulk, and it can enter the micron- and submicron-sized interparticle gaps between adjacent porous silicon primary particles. By selecting appropriate sheet diameter and thickness, the ability of the flexible nanographite crystallizer to fill the gaps between fine particles as well as its ability to overlap and bridge between sheets can be considered.
[0028] Preferably, the flexible nano-graphite crystals fill 30%-60% of the interparticle gaps; residual interparticle voids remain inside the secondary particles that are not filled by the flexible nano-graphite crystals. In this invention, the flexible nano-graphite crystals partially fill the interparticle gaps rather than completely filling them, so that while forming an interparticle conductive structure, a certain amount of residual interparticle voids are still retained inside the secondary particle body. These residual interparticle voids, together with the nanopores inside the porous silicon primary particles, form expansion buffer spaces of different sizes, which are beneficial for accommodating the volume changes of silicon during charging and discharging, reducing the compression between adjacent primary particles and the resulting particle breakage and conductive contact failure.
[0029] The interparticle gap filling rate can be determined by examining the secondary particle cross-section. Specifically, the material to be tested can be resin-embedded and a particle cross-section can be prepared. The porous silicon primary particles, flexible nano-graphite crystals, and residual voids between particles can be distinguished using scanning electron microscopy and / or transmission electron microscopy. The interparticle gap filling rate can be determined based on the area occupied by the flexible nano-graphite crystals and the area occupied by the residual voids between particles in the interparticle gap region.
[0030] An outer carbon coating layer is applied to the outer surface of the secondary particle body. This outer carbon coating layer comprises at least one of a graphite carbon layer, an amorphous carbon layer, or a carbon nanotube network layer. Preferably, the outer carbon coating layer is an amorphous carbon layer. This outer carbon coating layer can completely coat the secondary particle body from the outside, which helps maintain the structural integrity of the secondary particle body during charging and discharging, and reduces the continuous infiltration of electrolyte into the secondary particle body and the resulting interfacial side reactions.
[0031] The outer carbon coating layer has a thickness of 2-15 nm, and its coverage of the outer surface of the secondary particle host is no less than 90%. The thickness and coverage of the outer carbon coating layer strike a balance between surface protection, electron transport, and lithium-ion transport of the secondary particle host. A higher surface coverage of the outer carbon coating layer further reduces direct contact between the silicon material inside the secondary particle host and the electrolyte, and helps maintain the overall structural stability of the secondary particle.
[0032] The outer carbon coating layer, flexible nano-graphite crystals, and the pre-carbon coating layer on the surface of the porous silicon primary particles are electrically interconnected, forming a conductive network extending from the inside to the outside of the secondary particles. Specifically, the pre-carbon coating layer on the surface of the porous silicon primary particles is used to establish a conductive interface on the surface of a single particle. The flexible nano-graphite crystals between particles are used to establish conductive bridges between different porous silicon primary particles, further forming a three-dimensional conductive structure inside the secondary particle body. The outer carbon coating layer is connected to the aforementioned internal conductive structure. This allows the electron transport path to extend from the surface of a single porous silicon primary particle through the flexible nano-graphite crystals to the outer surface of the secondary particle body, thus forming a multi-level, interconnected electron transport path and improving the stability of the overall conductive structure of the secondary particles during high-rate charging and discharging.
[0033] The high-rate silicon anode material of this invention can be obtained by the following preparation method. The main steps are as follows: S1. The porous silicon primary particles are pretreated, and a pre-carbon coating layer is formed on the surface of the porous silicon primary particles by chemical vapor deposition to obtain pre-carbon coated porous silicon primary particles.
[0034] Specifically, the porous silicon primary particles are immersed and cleaned in a mixed purification reagent composed of anhydrous ethanol and dilute hydrofluoric acid for 5-30 min at a temperature of 20-40 °C to remove the oxide layer and residual impurities on the surface of the porous silicon primary particles. After cleaning, the particles are filtered and washed with anhydrous ethanol and / or deionized water, and then vacuum dried at 60-120 °C for 4-12 h to remove residual moisture and solvent on the surface and in the pores of the porous silicon primary particles. The purified and dried porous silicon primary particles are placed in the reaction zone of a chemical vapor deposition (CVD) apparatus. An inert gas is first introduced for atmosphere replacement. Under inert gas protection, the temperature is raised to 600-800 °C, and then a gaseous carbon source, including at least one of methane, acetylene, or propylene, is introduced for CVD for 15-180 min. The total flow rate of the reaction gas is 50-200 mL / min, allowing carbon material to be deposited on the outer surface of the porous silicon primary particles, and partially deposited on the pore walls communicating with the outer surface of the particles, forming a continuous or nearly continuous pre-carbon coating layer with a thickness of 2-15 nm, while preserving the internal pore structure of the porous silicon primary particles. After the pre-carbon coating is completed, the particles are cooled to room temperature under an inert atmosphere.
[0035] Preferably, the porosity of the porous silicon primary particles is 20%-30%, and the particle size D50 is 0.2-2.0 μm.
[0036] In a specific example, the mass fraction of dilute hydrofluoric acid is 2%-5%, the volume ratio of dilute hydrofluoric acid to anhydrous ethanol is 1:3, the soaking and cleaning time is 10-20 min; the vacuum drying temperature is 80 ℃, the vacuum drying time is 6 h; the chemical vapor deposition temperature is 700 ℃, the deposition holding time is 15-80 min, the inert protective gas is argon, and the total flow rate of the reaction gas is 100 mL / min.
[0037] S2, flexible nano-graphite microcrystals and binder are dispersed in a solvent to obtain a filling slurry containing flexible nano-graphite microcrystals. Pre-carbon-coated porous silicon primary particles are mixed with the filling slurry to obtain a silicon-graphite mixed suspension.
[0038] Specifically, flexible nano-graphite crystals and a binder are added to a solvent and dispersed by high-speed stirring and / or shearing for 30-120 min to obtain a filled slurry containing flexible nano-graphite crystals. Then, the pre-carbon-coated porous silicon primary particles obtained in step S1 are gradually added to the filled slurry, and high-speed shearing and stirring are performed at 1000-5000 r / min for 1-4 h to obtain a silicon-graphite mixed suspension. Under the action of high-speed shearing and slurry wetting, the flexible nano-graphite crystals are dispersed between adjacent porous silicon primary particles and enter the micron- and submicron-sized interparticle gaps between adjacent porous silicon primary particles. The binder includes at least one of polyvinyl alcohol (PVA) or carboxymethyl cellulose (CMC), and the solvent includes deionized water or anhydrous ethanol. The apparent viscosity of the filled slurry at 25 °C is 500-5000 mPa·s, and the solid content is 5%-30%; the apparent viscosity is measured using a rotational viscometer under predetermined rotor and shear rate conditions.
[0039] By adjusting the amount of flexible nano-graphite crystals added and the viscosity and solid content of the filling slurry, the flexible nano-graphite crystals preferentially enter the interparticle gaps between adjacent porous silicon primary particles and partially fill the interparticle gaps. At the same time, some residual voids between particles that are not completely filled are retained to provide buffer space for volume changes during the subsequent silicon intercalation and deintercalation process, and to reduce the independent agglomeration of flexible nano-graphite crystals in the slurry and excessive accumulation on the outer surface of the particles.
[0040] Preferably, the flexible nano-graphite crystallite has a sheet diameter of 50-120 nm and a thickness of 3-10 nm, and the flexible nano-graphite crystallite accounts for 15%-40% of the total mass of the final high-rate silicon anode material.
[0041] In a preferred embodiment, the high-speed shear stirring speed is 2000-3000 r / min, and the shear stirring time is 2 h; the apparent viscosity of the filler slurry is 1000-3000 mPa·s, and the solid content is 8%-15%. When the viscosity of the filler slurry is lower than the set range, the viscosity can be increased by increasing the amount of binder, increasing the solid content of the flexible nano-graphite microcrystals, and / or reducing the amount of solvent; when the viscosity of the filler slurry is higher than the set range, the viscosity can be reduced by adding solvent and / or reducing the binder concentration.
[0042] S3, the silicon-graphite mixed suspension is desolvated and agglomerated to form a secondary particle body by agglomerating multiple porous silicon primary particles, resulting in a composite secondary particle body filled with flexible nano-graphite microcrystals.
[0043] Specifically, the silicon-graphite mixed suspension obtained in step S2 is desolventized and agglomerated to form a secondary particle body by agglomerating multiple pre-carbon-coated porous silicon primary particles, while flexible nano-graphite microcrystals are retained and distributed in the interparticle gaps between adjacent porous silicon primary particles, resulting in a composite secondary particle body filled with flexible nano-graphite microcrystals.
[0044] For solvent-free agglomeration molding, spray drying is preferred. A silicon-graphite mixed suspension is continuously fed into a spray drying device for atomization granulation. The inlet air temperature is 160-220 ℃, the outlet air temperature is 70-110 ℃, and the atomization pressure is 0.2-0.6 MPa. By adjusting the solid content of the silicon-graphite mixed suspension, the feed rate, the atomization pressure, and the spray drying temperature, the resulting composite secondary particles can have a near-spherical or quasi-spherical morphology.
[0045] By controlling the amount of flexible nano-graphite crystals added in step S2, the filling rate of the interparticle gaps between adjacent porous silicon primary particles is made 30%-60%, thus preventing the gaps from being completely filled and leaving some residual interparticle voids unfilled within the composite secondary particle body. These residual interparticle voids, together with the nanopores inside the porous silicon primary particles, provide a buffer space for the volume change of silicon during lithium insertion / extraction.
[0046] Preferably, the inlet air temperature of the spray dryer is 180-200 ℃, the outlet air temperature is 80-90 ℃, and the atomization pressure is 0.3-0.4 MPa.
[0047] S4. The composite secondary particle body is mixed with the carbon source coated with an outer carbon layer and then heat-treated to form an outer carbon coating layer on the outer surface of the composite secondary particle body, thus obtaining a high-rate silicon anode material.
[0048] Specifically, the composite secondary particle body obtained in step S3 is dry-mixed with the outer carbon-coated carbon source to ensure uniform distribution and adhesion of the outer carbon-coated carbon source to the outer surface of the composite secondary particle body. The mixed material is then placed in a tube furnace, atmosphere furnace, or other inert atmosphere heat treatment equipment, and heated to 850-1100 ℃ at a heating rate of 2-8 ℃ / min under nitrogen and / or argon protection, and held at this temperature for 1-5 h. This causes carbonization of the outer carbon-coated carbon source, forming an outer carbon coating layer on the outer surface of the composite secondary particle body. After heat treatment, the material is naturally cooled to room temperature under inert atmosphere protection, followed by mild depolymerization, sieving, and / or classification to obtain a high-rate silicon anode material.
[0049] Preferably, the carbon source for the outer carbon coating accounts for 2%-15% of the total mass of the final high-rate silicon anode material; the heat treatment temperature is 900-1000 ℃, the holding time is 2-3 h, the heating rate is 5 ℃ / min, the inert protective gas is nitrogen or argon, and the inert protective gas flow rate is 100 mL / min. The carbon source for the outer carbon coating includes at least one of coal tar pitch or petroleum pitch, and the thickness of the resulting outer carbon coating layer is 2-15 nm.
[0050] This invention involves sequentially performing pre-carbon coating on the surface of porous silicon primary particles, filling with flexible nano-graphite crystals, desolvation and agglomeration, and heat treatment for outer carbon coating. This allows the pre-carbon coating layer, the flexible nano-graphite crystals between particles, and the outer carbon coating layer to gradually form at predetermined positions, thereby constructing a multi-level conductive structure that continuously extends from the surface of single particles, the inter-particle region, to the outer surface of secondary particles. This preparation method can control the thickness of the pre-carbon coating layer, the distribution and filling degree of the flexible nano-graphite crystals, the particle size of the secondary particles, and the thickness of the outer carbon coating layer by controlling the chemical vapor deposition conditions, the viscosity and solid content of the filling slurry, the spray drying parameters, and the heat treatment conditions for outer carbon coating. This helps reduce independent agglomeration of flexible nano-graphite crystals and excessive accumulation on the outer surface, and improves the conductivity continuity, structural stability, rate performance, and cycle performance of the resulting high-rate silicon anode material while maintaining a certain buffer space within the particles.
[0051] The high-rate silicon anode material proposed in this invention can be used as a lithium-ion battery anode and applied in fields such as power batteries for new energy vehicles, energy storage lithium batteries, and consumer electronics lithium batteries.
[0052] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0053] Example 1 Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0054] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 30 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 8 nm.
[0055] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0056] The resulting mixed suspension was spray-dried and granulated at an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa, yielding porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, i.e., the composite secondary particle matrix. Particle size analysis showed that the particle size D50 of the obtained composite secondary particle matrix was approximately 10 μm; interparticle gap filling rate analysis showed that the flexible nano-graphite microcrystals filled the interparticle gaps in the range of 40%-45%.
[0057] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 6.6 g, yielding approximately 4.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection, held at that temperature for 2.5 h, and then cooled before depolymerization and sieving to obtain the high-rate silicon anode material of Example 1. The average thickness of the outer carbon coating layer was approximately 5 nm.
[0058] Example 2 The flexible nano-graphite microcrystal wafer diameter in this embodiment differs from that in Example 1, and is used to investigate the effect of the change in nano-graphite microcrystal wafer diameter on the filling effect of small gaps between particles and the conductive bridging structure.
[0059] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0060] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 30 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 8 nm.
[0061] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 60 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0062] The resulting mixed suspension was spray-dried and granulated at an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa, yielding porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, i.e., the composite secondary particle matrix. Particle size analysis showed that the particle size D50 of the obtained composite secondary particle matrix was approximately 10 μm; interparticle gap filling rate analysis showed that the flexible nano-graphite microcrystals filled the interparticle gaps in the range of 40%-45%.
[0063] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 6.6 g, yielding approximately 4.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection, held at that temperature for 2.5 h, and then cooled before depolymerization and sieving to obtain the high-rate silicon anode material of Example 2. The average thickness of the outer carbon coating layer was approximately 5 nm.
[0064] Example 3 The amount of flexible nano-graphite crystals added in this embodiment is different from that in Example 1, and is used to investigate the effect of the change in the amount of flexible nano-graphite crystals on the degree of filling between particles and the continuity of the three-dimensional conductive network inside the secondary particles.
[0065] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0066] The purified and dried porous silicon was placed in a tube furnace, with argon as the protective and carrier gas, and methane as the gaseous carbon source (methane volume fraction 10%). The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 30 min. A pre-carbon coating layer with an average thickness of approximately 8 nm was formed on the surface of each primary porous silicon particle.
[0067] 24.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 250 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0068] The resulting mixed suspension was spray-dried and granulated at an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa, yielding porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, i.e., the composite secondary particle matrix. Particle size analysis showed that the particle size D50 of the obtained composite secondary particle matrix was approximately 10 μm; interparticle gap filling rate analysis showed that the flexible nano-graphite microcrystals filled the interparticle gaps in the range of 55%-60%.
[0069] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 6.6 g, yielding approximately 4.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection, held at that temperature for 2.5 h, and then cooled before depolymerization and sieving to obtain the high-rate silicon anode material of Example 3. The average thickness of the outer carbon coating layer was approximately 5 nm.
[0070] Example 4 The thickness of the pre-carbon coating layer in this embodiment differs from that in Example 1, and is used to investigate the effect of a thinner pre-carbon coating layer on the surface protection, interfacial conductivity, and cycle stability of porous silicon primary particles.
[0071] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0072] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 15 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 4 nm.
[0073] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0074] The resulting mixed suspension was spray-dried and granulated with an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa to obtain porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, which are the main body of composite secondary particles.
[0075] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 6.6 g, yielding approximately 4.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection, held at that temperature for 2.5 h, and then cooled before depolymerization and sieving to obtain the high-rate silicon anode material of Example 4. The average thickness of the outer carbon coating layer was approximately 5 nm.
[0076] Example 5 The thickness of the pre-carbon coating layer in this embodiment differs from that in Example 1, and is used to investigate the effects of a thicker pre-carbon coating layer on the surface isolation of porous silicon primary particles, electron transport performance, active silicon content, and material specific capacity.
[0077] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0078] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 60 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 15 nm.
[0079] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0080] The resulting mixed suspension was spray-dried and granulated with an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa to obtain porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, which are the main body of composite secondary particles.
[0081] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 6.6 g, yielding approximately 4.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection and held at that temperature for 2.5 h. After cooling, depolymerization and sieving were performed to obtain the high-rate silicon anode material of Example 5. The average thickness of the outer carbon coating layer was approximately 5 nm.
[0082] Example 6 The thickness of the outer carbon coating layer in this embodiment differs from that in Example 1, and is used to investigate the effect of a thinner outer carbon coating layer on the integrity of the secondary particle structure, electrolyte isolation capability, initial coulombic efficiency, and rate performance.
[0083] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0084] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 30 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 8 nm.
[0085] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0086] The resulting mixed suspension was spray-dried and granulated with an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa to obtain porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, which are the main body of composite secondary particles.
[0087] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 3.3 g, yielding approximately 2.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection and held at that temperature for 2.5 h. After cooling, depolymerization and sieving were performed to obtain the high-ratio silicon anode material of Example 6. Statistical analysis of multiple particles using transmission electron microscopy showed that the average thickness of the obtained outer carbon coating layer was approximately 2-3 nm.
[0088] Example 7 The thickness of the outer carbon coating layer in this embodiment differs from that in Example 1, and is used to investigate the effect of a thicker outer carbon coating layer on the mechanical strength, surface stability, electronic conductivity, initial coulombic efficiency, and specific capacity of the secondary particles.
[0089] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, add it to a mixed purification solution of 3% by mass of dilute HF and anhydrous ethanol, wherein the volume ratio of dilute HF to anhydrous ethanol is 1:3, and soak and wash at 25 ℃ for 15 min; after washing, filter, wash with anhydrous ethanol, and vacuum dry at 80 ℃ for 6 h.
[0090] The purified and dried porous silicon was placed in a tube furnace, using argon as both a protective and carrier gas, and methane (10% by volume) as the gaseous carbon source. The temperature was raised to 700 °C, and chemical vapor deposition was performed at this temperature for 30 min. Transmission electron microscopy revealed that the average thickness of the pre-carbon coating layer formed on the surface of a single porous silicon primary particle was approximately 8 nm.
[0091] 18.0 g of flexible nano-graphite crystals with a sheet thickness of approximately 5 nm and an average sheet diameter of approximately 80 nm were added to 200 mL of deionized water, along with 1.0 g of CMC. The mixture was dispersed at high speed for 60 min to prepare a flexible nano-graphite crystal filling slurry. The pre-carbon-coated porous silicon was then added to the filling slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h to allow the flexible nano-graphite crystals to fully penetrate the interparticle gaps between adjacent porous silicon primary particles, resulting in a silicon-graphite mixed suspension.
[0092] The resulting mixed suspension was spray-dried and granulated with an inlet air temperature of 190 ℃, an outlet air temperature of 85 ℃, and an atomization pressure of 0.35 MPa to obtain porous silicon agglomerated microspheres filled with flexible nano-graphite microcrystals, which are the main body of composite secondary particles.
[0093] Coal tar pitch was added to the obtained composite secondary particle matrix for overall outer coating. Based on the measured residual carbon rate of approximately 60% at 950℃, the amount of coal tar pitch added was 13.3 g, yielding approximately 8.0 g of outer coated carbon. After uniform mixing, the mixture was heated to 950℃ at a rate of 5℃ / min under argon protection and held at that temperature for 2.5 h. After cooling, depolymerization and sieving were performed to obtain the high-ratio silicon anode material of Example 7. Statistical analysis of multiple particles using transmission electron microscopy showed that the average thickness of the obtained outer carbon coating layer was approximately 8-10 nm.
[0094] Comparative Example 1 This comparative example does not contain flexible nano-graphite crystals and is used to evaluate the effect of the interstitial filling and conductive bridging structure between flexible nano-graphite crystal particles on cycle stability and rate performance.
[0095] The purification process and pre-carbon coating steps for the porous silicon powder were exactly the same as in Example 1. The difference from Example 1 was that flexible nano-graphite crystals were not added to fill the interparticle gaps. The pre-carbon-coated porous silicon was added to 200 mL of deionized water containing 1.0 g of CMC and subjected to high-speed shearing and stirring at 2500 r / min for 2 h, followed by spray granulation under the same conditions as in Example 1.
[0096] The resulting secondary particle body was mixed with 6.6 g of coal tar pitch and heated to 950 °C at 5 °C / min under argon protection, held for 2.5 h, and then cooled, depolymerized and sieved to obtain the material of Comparative Example 1.
[0097] Comparative Example 2 This comparative example uses micron-sized flake graphite instead of flexible nano-graphite crystallites to evaluate the role of flexible nano-graphite crystallites in filling small gaps between particles and bridging electrical conduction across particles compared to ordinary micron-sized flake graphite.
[0098] The purification process and pre-carbon coating steps for the porous silica powder were exactly the same as in Example 1. The difference from Example 1 was that 18.0 g of ordinary micron-sized flake graphite with a D50 of approximately 3 μm was replaced with flexible nano-graphite crystals.
[0099] The flake graphite was added to 200 mL of deionized water, and 1.0 g of CMC was added. The mixture was dispersed at high speed for 60 min. Pre-carbon-coated porous silicon was then added, and the mixture was sheared and stirred at high speed at 2500 r / min for 2 h. The remaining spray granulation, coal tar coating, and final heat treatment processes were the same as in Example 1, resulting in the material of Comparative Example 2.
[0100] Comparative Example 3 This comparative example does not involve pre-coating of the primary particles and is used to evaluate the effect of the pre-carbon coating layer on the surface of a single porous silicon primary particle on inhibiting direct contact between silicon and electrolyte, improving interfacial conductivity, stabilizing the solid electrolyte interfacial film, and improving cycle stability.
[0101] Take 50.0 g of porous silica powder with a porosity of 25% and a particle size D50 of 1.0 μm, and purify it with a mixture of dilute HF and anhydrous ethanol under the same conditions as in Example 1, followed by filtration, washing with anhydrous ethanol and vacuum drying.
[0102] Unlike Example 1, the purified and dried porous silicon powder is not subjected to methane chemical vapor deposition treatment, that is, no pre-carbon coating layer is formed on the surface of a single porous silicon primary particle.
[0103] Take 18.0 g of flexible nano-graphite microcrystals with a sheet thickness of about 5 nm and an average sheet diameter of about 80 nm, add them to 200 mL of deionized water, add 1.0 g of CMC, and disperse at high speed for 60 min to obtain flexible nano-graphite microcrystal filling slurry.
[0104] Uncoated porous silica powder was gradually added to the filler slurry and subjected to high-speed shearing and stirring at 2500 r / min for 2 h. Subsequently, it was spray-dried and granulated under the same conditions as in Example 1.
[0105] 6.6 g of coal tar pitch was added to the obtained secondary particle matrix, and after thorough mixing, the mixture was heated to 950 °C at a heating rate of 5 °C / min under argon protection and held at that temperature for 2.5 h. After cooling, depolymerization and sieving were performed to obtain the material of Comparative Example 3.
[0106] The materials obtained from the examples and comparative examples were tested according to the following test methods, and their performance was evaluated.
[0107] 1. Initial discharge specific capacity and initial coulombic efficiency test The negative electrode materials prepared in the examples and comparative examples were mixed with Super P and sodium carboxymethyl cellulose binder at a mass ratio of 8:1:1. Deionized water was added to form a slurry, which was then uniformly coated onto copper foil. After vacuum drying at 80 °C for 12 h, the mixture was rolled and punched to obtain the negative electrode sheet. Using a lithium metal sheet as the counter electrode and a 1 mol / L LiPF6 mixed solution of ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) as the electrolyte, with a volume ratio of EC, DMC, and EMC of 1:1:1, a CR2032 coin cell was assembled in an inert gas glove box.
[0108] The Blue Battery Testing System was used to conduct constant current charge-discharge tests at a rate of 0.2 C within a voltage range of 0.005-1.5 V, and the initial lithium insertion specific capacity and the initial lithium extraction specific capacity were recorded.
[0109] Initial coulombic efficiency (%) = Initial delithiation specific capacity ÷ Initial lithiation specific capacity × 100%.
[0110] 2. Cyclic stability test Using the assembled button cells described above, constant current charge-discharge cycle tests were conducted at a rate of 0.5 C within a voltage range of 0.005-1.5 V. The discharge specific capacity after 100 cycles was recorded, and the capacity retention rate was calculated.
[0111] Capacity retention rate (%) = discharge specific capacity after 100 cycles ÷ initial discharge specific capacity × 100%.
[0112] 3. Ratio Performance Test Using the coin cell assembled above, constant current charge-discharge tests were conducted at rates of 0.1 C, 0.2 C, 0.5 C, 1 C and 2 C within a voltage range of 0.005-1.5 V. The discharge specific capacity at different rates was recorded, and the capacity retention rate at 2 C / 0.1 C was calculated to characterize the rate performance of the material.
[0113] Rate capacity retention rate (%) = 2C rate discharge specific capacity ÷ 0.1C rate discharge specific capacity × 100%.
[0114] 4. Particle size testing methods The particle size of the primary and secondary porous silicon particles was determined using a laser particle size analyzer. The particle size corresponding to a cumulative volume distribution of 50% was denoted as D50.
[0115] 5. Particle gap filling rate test The composite secondary particle material to be tested was embedded in resin, and the cross-section of the secondary particles was prepared by ion beam cutting or ion milling.
[0116] The internal cross-section of the secondary particles was observed using scanning electron microscopy or transmission electron microscopy. Combined with the lamellar morphology of flexible nano-graphite crystals and necessary elemental surface scanning or structural characterization, the porous silicon primary particles, the flexible nano-graphite crystals between particles, and the residual voids between particles were distinguished.
[0117] In the secondary particle cross-section, the interparticle gap region enclosed by the boundaries of adjacent porous silicon primary particles was selected, excluding the nanopores inside the porous silicon primary particles. Image analysis software was used to statistically analyze the area A1 occupied by flexible nano-graphite microcrystals in the interparticle gap region and the area A2 of residual interparticle voids not filled by solid material.
[0118] The interparticle gap filling rate is calculated according to the following formula: Particle gap filling rate (%) = A1 ÷ (A1 + A2) × 100%.
[0119] For each sample, multiple representative secondary particle cross sections were randomly selected for statistical analysis, and the average value of the calculated results for each statistical region was used as the particle gap filling rate of that sample.
[0120] The test results are recorded in Tables 1 and 2.
[0121] Table 1. Initial charge-discharge performance and cycle performance test results of the examples and comparative examples. Table 2. Rate performance test results of the examples and comparative examples. Figure 2 This is a graph comparing the cycle performance of Example 1 and Comparative Example 1 of the present invention. Figure 3 This is a rate performance curve of Embodiment 1 of the present invention.
[0122] According to Table 1, Table 2 and Figure 2 and Figure 3As can be seen, the anode material obtained in Example 1 exhibits high initial reversible specific capacity, cycle capacity retention, and rate capacity retention, demonstrating relatively balanced comprehensive electrochemical performance. This indicates that by setting a pre-carbon coating layer on the surface of a single porous silicon primary particle and filling the spaces between adjacent porous silicon primary particles with flexible nano-graphite crystals, the flexible nano-graphite crystals can form relatively continuous inter-particle conductive bridges through mutual overlap, thereby improving the electron transport capability within the composite secondary particles. Simultaneously, some residual voids remain between the particles, providing a buffer space for volume changes in the silicon material during lithium insertion and extraction, reducing the risk of inter-particle compression, breakage, and conductive contact failure. Therefore, Example 1 maintains a high initial reversible capacity while exhibiting good cycle stability and high-rate charge / discharge capability.
[0123] Example 2 uses flexible nano-graphite crystals with a smaller average sheet diameter. Its initial lithium insertion and extraction specific capacities are basically similar to those of Example 1, indicating that with the same amount of flexible nano-graphite crystals added, reducing the average sheet diameter from approximately 80 nm to approximately 60 nm does not significantly change the active silicon content and low-rate reversible capacity of the composite material. Smaller-diameter flexible nano-graphite crystals can enter smaller interparticle gaps, which is beneficial for filling these gaps; however, as the sheet diameter decreases, the ability to form continuous overlaps and cross-particle bridges between sheets may be affected. Example 2 has a discharge specific capacity of 1235 mAh / g at 2 C rate, and a 2 C / 0.1 C rate capacity retention of 68.99%, slightly lower than Example 1. This result shows that smaller sheet diameters are not necessarily more advantageous for flexible nano-graphite crystals; a moderate sheet diameter is more conducive to balancing interparticle gap filling, sheet overlap, and conductive network continuity.
[0124] Example 3 increased the amount of flexible nano-graphite crystallites. Due to the increased mass proportion of low-specific-capacity graphite components in the composite material and the decreased relative content of active silicon, the initial lithium insertion and extraction specific capacities of the material decreased. However, the capacity retention rate after 100 cycles in Example 3 increased to 81.63%, and the 2C / 0.1C rate capacity retention rate increased to 79.29%, indicating that increasing the amount of flexible nano-graphite crystallites increases the number and connectivity of conductive bridges between particles and facilitates the formation of a more continuous internal three-dimensional conductive network. Therefore, increasing the amount of flexible nano-graphite crystallites is beneficial for improving cycle performance and rate performance. However, excessive flexible nano-graphite crystallites will reduce the relative proportion of active silicon in the material and decrease residual voids between particles. Therefore, it is necessary to comprehensively consider reversible capacity, conductive network continuity, and expansion buffer space.
[0125] Example 4 uses a thinner pre-carbon coating layer. Due to the reduced thickness of the pre-carbon coating layer, the mass percentage of carbon components in the composite material decreases, while the relative mass percentage of active silicon increases, thus maintaining a high initial lithium insertion and extraction specific capacity. However, the thinner pre-carbon coating layer relatively weakens the covering and protection effect on the surface of the porous silicon primary particles, and its inhibitory effect on direct contact between the electrolyte and the porous silicon surface is also relatively limited. Simultaneously, the thinner pre-carbon coating layer has a relatively weaker effect on improving the conductivity continuity of individual porous silicon primary particle surfaces. Therefore, Example 4 has an initial coulombic efficiency of 82.14%, a capacity retention rate of 72.55% after 100 cycles, and a 2C / 0.1C rate capacity retention rate of 63.91%, all lower than Example 1. This result indicates that an appropriate pre-carbon coating layer thickness is beneficial for balancing active silicon content, interface protection, and electron transport performance of individual particle surfaces.
[0126] Example 5 employs a thicker pre-carbon coating layer. A thicker pre-carbon coating layer can more fully cover the surface of the porous silicon primary particles, reducing direct contact between silicon and the electrolyte, and is beneficial for maintaining the stability of the conductive interface on the surface of the porous silicon primary particles. Therefore, the initial coulombic efficiency of Example 5 is 85.61%, and the capacity retention after 100 cycles is 82.62%, both higher than that of Example 1. However, the increased pre-carbon coating layer thickness increases the carbon component ratio and reduces the relative mass ratio of active silicon in the composite material; therefore, the initial delithiation specific capacity of Example 5 is 1755 mAh / g, lower than that of Example 1. The 2C / 0.1C rate capacity retention of Example 5 is 73.34%, still maintaining good rate performance. This indicates that increasing the thickness of the pre-carbon coating layer is beneficial for improving interface stability and cycle stability, but its thickness still needs to balance the material's specific capacity and rate performance.
[0127] Example 6 uses a thinner outer carbon coating layer. Due to the lower carbon content in the outer layer, the relative mass proportion of active silicon in the material is higher, thus maintaining a high initial lithium insertion and initial lithium extraction specific capacity. However, the thinner outer carbon coating layer provides relatively insufficient overall coating and interface protection for the composite secondary particle body, and its external connection and maintenance of the internal conductive structure are also relatively weak. The capacity retention rate after 100 cycles in Example 6 is 72.53%, and the capacity retention rate at 2 C / 0.1 C is 61.90%, both lower than that in Example 1. This result indicates that an excessively thin outer carbon coating layer is detrimental to maintaining the overall structure, surface stability, and continuity of the internal and external conductive networks of the composite secondary particles.
[0128] Example 7 employs a thicker outer carbon coating layer. A thicker outer carbon coating layer improves the overall coating degree of the composite secondary particles, reduces direct contact between the electrolyte and the internal silicon material, and helps maintain the external electron transport pathway and overall structural stability of the secondary particles. Example 7 achieved an initial coulombic efficiency of 86.92% and a capacity retention rate of 84.66% after 100 cycles, both higher than Example 1. However, the increased thickness of the outer carbon coating layer increases the mass proportion of the low-specific-capacity carbon component, leading to a decrease in the relative mass proportion of active silicon. Therefore, the initial lithium insertion specific capacity and initial lithium extraction specific capacity of Example 7 were 1950 mAh / g and 1695 mAh / g, respectively, lower than Example 1. Its 2C / 0.1C rate capacity retention rate was 72.29%, maintaining good rate performance. This indicates that appropriately increasing the thickness of the outer carbon coating layer is beneficial for improving interface and cycle stability, but an excessively thick outer carbon coating layer can have a certain impact on the material's specific capacity.
[0129] Comparative Example 1 did not contain flexible nano-graphite crystals. Its initial lithium-intercalation specific capacity was relatively high, mainly because no additional graphite component was introduced into the material, resulting in a higher mass ratio of active silicon. However, its initial coulombic efficiency was only 78.22%, and the capacity retention after 100 cycles and at 2 C / 0.1 C rate decreased to 63.07% and 42.86%, respectively. In Table 2, the discharge specific capacity of Comparative Example 1 at 2 C rate was only 735 mAh / g, significantly lower than the 1285 mAh / g of Example 1. This result indicates that relying solely on the pre-carbon coating layer on the surface of a single porous silicon primary particle and the outer carbon coating layer on the outer surface of the secondary particle body is insufficient to form a sufficient and continuous cross-particle conductive pathway within the secondary particle; the inter-particle conductive bridges formed by flexible nano-graphite crystals play a crucial role in improving the continuity of electron transport and rate performance within the composite material.
[0130] Comparative Example 2 used micron-sized flake graphite instead of flexible nano-graphite crystals. Its capacity retention after 100 cycles was 63.02%, its 2C / 0.1C rate capacity retention was 39.39%, and its 2C rate discharge specific capacity was 650 mAh / g, all significantly lower than Examples 1 and 2. The size of ordinary micron-sized flake graphite is significantly larger than that of flexible nano-graphite crystals, making it difficult to fully penetrate the micron- and submicron-sized interparticle gaps between adjacent porous silicon primary particles. Therefore, it is difficult to form a sufficient number and uniformly distributed cross-particle conductive bridges between multiple adjacent primary particles. The resulting internal conductive network is weak in terms of uniformity, continuity, and cycle stability. These results demonstrate that simply introducing graphite conductive materials is insufficient to achieve the technical effects of this invention. The nanoscale of the flexible nano-graphite crystals and the resulting interparticle filling and bridging structures play a crucial role in improving rate performance and cycle performance.
[0131] Comparative Example 3 did not have a pre-carbon coating layer on the surface of the individual porous silicon primary particles. Although its composite secondary particle body still contained flexible nano-graphite crystals and had an outer carbon coating layer on its outer surface, the flexible nano-graphite crystals were mainly used to establish conductive bridges between adjacent primary particles, and the outer carbon coating layer was mainly used to form the overall coating and conductive structure of the secondary particles. Neither of these can replace the pre-carbon coating layer directly applied to the surface of the individual porous silicon primary particles. Due to the lack of a pre-carbon coating layer, the direct contact between the surface of the porous silicon primary particles and the electrolyte increased, leading to an increase in interfacial side reactions during the first lithium insertion process. Therefore, the initial coulombic efficiency of Comparative Example 3 was only 73.92%, the capacity retention rate after 100 cycles was 52.48%, and the 2C / 0.1C rate capacity retention rate was 31.23%, all significantly lower than that of Example 1. This result indicates that the pre-carbon coating layer plays an important role in reducing the direct contact between the porous silicon primary particles and the electrolyte, improving the conductivity of the individual particle surface, and enhancing interfacial and cycle stability.
[0132] The test results from the combined examples and comparative examples show that the electrochemical performance of the high-rate silicon anode material of the present invention is not determined by a single carbon structure, but rather by the combined effect of the pre-carbon coating layer on the surface of the porous silicon primary particles, the conductive bridging structure formed by the flexible nano-graphite microcrystals between the particles, and the outer carbon coating layer on the outer surface of the secondary particle body. Specifically, the pre-carbon coating layer reduces the direct contact between the porous silicon primary particles and the electrolyte and improves the electron transport performance of a single particle surface; the flexible nano-graphite microcrystals can penetrate the interparticle gaps between adjacent porous silicon primary particles, forming a three-dimensional conductive structure inside the secondary particles through overlapping, interlocking, and / or bridging, while retaining some residual interparticle voids to provide a buffer space for volume changes in the silicon material; the outer carbon coating layer can form an overall coating on the secondary particle body and is electrically connected to the internal flexible nano-graphite microcrystals and the pre-carbon coating layer. This forms an internally and externally interconnected conductive network extending from the surface of a single particle, through the interparticle region, to the outer surface of the secondary particles, enabling the material to maintain high reversible capacity while exhibiting good initial coulombic efficiency, cycle stability, and rate performance.
[0133] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-rate silicon anode material, characterized in that, The negative electrode material includes composite secondary particles, which include: a secondary particle body formed by the aggregation of multiple porous silicon primary particles, flexible nano-graphite microcrystals, and an outer carbon coating layer. The surface of the porous silicon primary particles has a pre-carbon coating layer; There are interparticle gaps between adjacent porous silicon primary particles, and the flexible nano-graphite crystals are distributed in the interparticle gaps; wherein, at least some of the flexible nano-graphite crystals are in contact with the pre-carbon coating layer on the surface of two or more adjacent porous silicon primary particles at the same time, forming a conductive bridge between adjacent porous silicon primary particles; and the flexible nano-graphite crystals form a three-dimensional conductive structure inside the secondary particles through overlapping, interlocking and / or bridging. The outer carbon coating layer covers the outer surface of the secondary particle body; the outer carbon coating layer, the flexible nano-graphite microcrystals, and the pre-carbon coating layer on the surface of the porous silicon primary particles are electrically connected to each other, forming a conductive network that extends from the inside to the outside of the secondary particles.
2. The high-rate silicon anode material according to claim 1, characterized in that, The porous silicon primary particles account for 50%-80% of the mass percentage of the high-rate silicon anode material, the flexible nano-graphite microcrystals account for 15%-40% of the mass percentage of the high-rate silicon anode material, and the outer carbon coating layer accounts for 2%-15% of the mass percentage of the high-rate silicon anode material.
3. The high-rate silicon anode material according to claim 1, characterized in that, The porous silicon primary particles have a particle size D50 of 0.2-2.0 μm; the porous silicon primary particles have multiple nanopores inside, at least some of which are interconnected, the average pore size of which is 5-100 nm, and the porosity of the porous silicon primary particles is 20%-30%. The pre-carbon coating layer covers the surface of the porous silicon primary particles, and the thickness of the pre-carbon coating layer is 2-15 nm.
4. The high-rate silicon anode material according to claim 1, characterized in that, The flexible nano-graphite crystallizer comprises sheet-like stacked crystals, with a sheet diameter of 20-200 nm and a thickness of 2-20 nm. The flexible nano-graphite microcrystals fill 30%-60% of the gaps between the particles; The secondary particles retain residual interparticle voids that were not filled by the flexible nano-graphite microcrystals.
5. The high-rate silicon anode material according to claim 1, characterized in that, The particle size D50 of the secondary particle body is 5-15 μm; The outer carbon coating layer has a thickness of 2-15 nm, and the outer carbon coating layer covers at least 90% of the outer surface of the secondary particle body. The outer carbon coating layer includes at least one of the following: a graphite carbon layer, an amorphous carbon layer, or a carbon nanotube network layer.
6. A method for preparing a high-rate silicon anode material according to any one of claims 1-5, characterized in that, The preparation method includes: S1, pre-treat the porous silicon primary particles and form a pre-carbon coating layer on the surface of the porous silicon primary particles by chemical vapor deposition to obtain pre-carbon coated porous silicon primary particles. S2, the flexible nano-graphite microcrystals and binder are dispersed in a solvent to obtain a filling slurry containing the flexible nano-graphite microcrystals, and the pre-carbon-coated porous silicon primary particles are mixed with the filling slurry to obtain a silicon-graphite mixed suspension. S3, the silicon-graphite mixed suspension is desolvated and agglomerated to form a secondary particle body by agglomerating multiple porous silicon primary particles, thereby obtaining a composite secondary particle body filled with flexible nano-graphite microcrystals; wherein, the flexible nano-graphite microcrystals are filled in the interparticle gaps between adjacent porous silicon primary particles. S4, the composite secondary particle body is mixed with the outer carbon-coated carbon source and heat-treated to form an outer carbon coating layer on the outer surface of the composite secondary particle body, thereby obtaining the high-rate silicon anode material.
7. The preparation method according to claim 6, characterized in that, In step S1, the pretreatment includes: purifying and cleaning the porous silicon primary particles; placing the pretreated porous silicon primary particles in a chemical vapor deposition (CVD) apparatus, introducing a gaseous carbon source under inert gas protection, and performing CVD at 600-800 °C for 15-180 min to form a pre-carbon coating layer with a thickness of 2-15 nm on the surface of the porous silicon primary particles; wherein the gaseous carbon source includes at least one of methane, acetylene, or propylene. In step S2, the binder includes at least one of polyvinyl alcohol (PVA) or carboxymethyl cellulose (CMC), and the solvent includes deionized water or anhydrous ethanol; the dispersion time is 30-120 min; the mixing is performed by high-speed shear stirring at a speed of 1000-5000 r / min for 1-4 h. In step S3, the method for desolventizing and agglomerating includes spray drying; the inlet air temperature of the spray drying is 160-220 ℃, the outlet air temperature is 70-110 ℃, and the atomization pressure is 0.2-0.6 MPa; In step S4, the mixing is a dry mixing process, and the carbon source for the outer carbon coating includes at least one of coal tar pitch or petroleum pitch; the heat treatment is carried out under an inert atmosphere, with a heating rate of 2-8 ℃ / min, a heat treatment temperature of 850-1100℃, and a holding time of 1-5 h.
8. The preparation method according to claim 6, characterized in that, In step S2, the apparent viscosity of the filler slurry at 25 °C is 500-5000 mPa·s; the solid content of the filler slurry is 5%-30%.
9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the high-rate silicon negative electrode material as described in any one of claims 1-4.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Porous silicon-carbon composite negative electrode material and preparation method and application thereof
CN120308967A